The Clinical Features of Patients with Chronic Hepatitis C Virus Infections Are Associated with Killer Cell Immunoglobulin-Like Receptor Genes and Their Expression on the Surface of Natural Killer Cells - Podhorzer, Ariel; Dirchwolf, Melisa; Machicote, Andrés; Belen, Santiago; Montal, Silvina; Paz, Silvia; Fainboim, Hugo; Podestá, Luis G.; Fainboim, Leonardo (Frontiers in Immunology, 2018)
Killer cell immunoglobulin-like receptor (KIR) genes are known to play a role in the acute phase of hepatitis C virus (HCV) infection. The present study investigated their roles in chronic HCV (CHCV) infection by analyzing the phenotypes and function of natural killer (NK) and T cells that express KIRs. T cells from CHCV patients showed a more differentiated phenotype, and NK cells exhibited an activated profile. These observations are consistent with the increased expression of the degranulation marker CD107a observed after PMA stimulation. We explored the correlations between the expression of KIR genes and lectin type-C receptors with clinical factors that predict progression to fibrosis and cirrhosis. The expression levels of KIR2DS3 and the functional alleles of KIR2DS4-FL were increased in patients with intermediate and high viral loads. Homozygous KIR2DS4 was also associated with the presence of cirrhosis. In the group of individuals with a shorter infection time who developed cirrhosis, we detected decreased expression of KIR3DL1 in CD56dim NK cells in the presence of its ligand. Similarly, in the group of patients with late CHCV infections complicated with cirrhosis, we detected lower expression of the strong inhibitory receptor NKG2A in CD56bright NK cells. We also detected an increase in NKG2C expression in CD56dim NK cells in CHCV patients who displayed high necroinflammatory activity. Decreased KIR3DL2 expression in CD56dim and CD56bright NK cells was associated with a high body mass index, and KIR3DL2 expression may be one factor associated with the more rapid progression of CHCV to fibrosis in patients.